MEDIA POP UP BOOK UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PADA ANAK USIA DINI - Aisyah Raudhatul Jannah; Lukman Hamid; Rostika Srihilmawati (Sekolah Tinggi Agama Islam (STAI) Al Hidayah Tasikmalaya, 2020)
This article contains pop up book media to improve reading skills in early childhood. The problem encountered was that early childhood experienced difficulties in recognizing letter symbols. Early childhood cannot distinguish one letter from another, and there is still incorrect pronunciation of letters in reading. This happens one of them caused by inaccurate media used in the learning process. In overcoming this problem, the authors took the initiative to use pop up book media as an alternative media for learning to read. In this paper using a descriptive method with a qualitative approach. The author describes the facts or circumstances or symptoms that appear as they are.